Exponential-Offset Modelling and XRD Correlation of SOH Degradation in LiFePO4 Batteries under Extreme Loading - Latif, Chaironi; Maulana, Tubagus Adam Jody; Yogianto, Mohammad Fahmi Ilmi; Adziimaa, Ahmad Fauzan (Journal of Energy, Material, and Instrumentation Technology, 2025)
Understanding the relationship between electrochemical degradation and structural changes is critical for improving the reliability of lithium-ion batteries. In this study, the state of health (SOH) of 18650-type lithium iron phosphate (LiFePO4, LFP) cells was evaluated under extreme loading using discharge resistances of 2.5 Ω and 0.005 Ω. The SOH decreased sharply after the first cycle and then declined more gradually, and the degradation trend was well described by an exponential-offset model with RMSE = 2.87, MAE = 2.25, and R2 = 0.90. Structural analysis was performed by X-ray diffraction (XRD) on electrode samples taken after one discharge at 2.5 Ω (L1), 100 discharges at 2.5 Ω (L100), and one discharge at 0.005 Ω (LD). The XRD results confirmed that the main phase was graphite, but with reduced peak intensities, peak broadening, and increased background noise, indicating crystallinity loss and partial amorphization. These findings demonstrate that SOH degradation is strongly correlated with the decline in crystallinity, and that extreme loading can trigger significant structural deterioration even within a single discharge.